General geology and structural analysis using resistivity method at Kampung Belanga, Kuala Krai, Kelantan - Siti Sa’adiah Abdul Latiff (2017)
This research was conducted at Kampung Belanga, which it was located in Kuala Krai, Kelantan. The objectives of this research were to produce the new geological map with scale of 1:25000 and also analyze the geology structure that existed in the study area by conducting the resistivity method. The research began with the interpretation of an aerial photo in order to determine the lineament structure of Kampung Belanga in order to know the presence of a structure and followed by the geological mapping. Through geological mapping, the lithologies and the structural geology of the study area were being identified. There were four different of rocks that have been categorized into two types which are igneous and sedimentary rocks. Those rocks are granite, sandstone, basalt and diorite and were in the era of Paleozoic to Cenozoic. Based on the stratigraphic column, granite shows the youngest among those rocks that existed in the study area. This is because, it intruded during the formation of rocks. For the structural analysis, fault and joint were being identified. It was a normal fault was being discovered with the concept of horst and graben in the study area. From the collecting data, the interpretation was being further analyzed by using stereonet analysis. Thus, it can be concluded that the main force of the fault movement came from the direction of NNE-SSW. Moreover, the presence of joint were also being identified in the study area. Two types of joint were found which are extension and shear joint. Besides that, two types of joint system were being recognized in the study area and they were systematic and non systematic. The interpretation of joint analysis was done by using rose diagram in order to know the direction of the force. In addition, by using the resistivity method, the presence of the subsurface can be identified and the results were being inverted by using RES2DINV software. Through resistivity method the blue zone based on pseudosection, the weak zone of the study area were being identified.